Quociente de inteligência de crianças e adolescentes obesos através da escala Wechsler Intelligent quotient of obese children and adolescents by the Weschler scale - Alba L. R. Campos; Dirce M. Sigulem; Denise E. B. Moraes; Arlete M. S. Escrivão; Mauro Fisberg (Universidade de São Paulo, 1996)
Foram estudadas as características intelectuais de 65 crianças obesas, de 8 a 13 anos e 11 meses, comparativamente às de 35 crianças eutróficas, através da Escala de Inteligência Wechsler para Crianças. Os dois grupos foram pareados de acordo com a faixa etária, série escolar e nível socioeconômico. O grupo de obesos foi composto por pacientes atendidos pelo Departamento de Pediatria da Universidade Federal São Paulo, e o grupo-controle, por crianças pertencentes a escolas públicas. O grupo de eutróficos apresentou significantemente melhor desempenho no teste de inteligência do que o grupo de obesos (Quociente de inteligência -QI médio - 91 x 85; p < 0,05). Crianças eutróficas revelaram maior amplitude de interesses e capacidade de adaptação social e, melhor velocidade e destreza. Houve correlação positiva entre o nível de renda, a relação peso/estatura e o QI. Apesar de todos os resultados médios de QI apresentarem dados consistentemente favoráveis aos eutróficos, não se pode afirmar total superioridade desse grupo em virtude da ampla gama de fatores emocionais intervenientes no processo de inteligência, não controlados pelo estudo. The intellectual characteristics of 65 obese children and adolescents (weight for height ³140% ), aged 8 to 13 years and 11 months, were compared to those of 35 eutrophic children and adolescents (weight for height between 90 and 110%; and stature for age > 95%) of the same age group, utilizing the Wechsler Intelligence Scale for Children - WISC. Children and adolescents of the two groups were paired according to age groups, schooling level and socioeconomic condition. The obese group was composed of new patients assisted at the Department of Pediatrics of the Federal University of S. Paulo (Escola Paulista de Medicina), Brazil. The control group was made up of children from public primary schools, from the same geographical area as those studied. The eutrophic group presented significantly better performance in the intelligence test (Intelligence Quotient - IQ) than the obese group (average IQ - 91 x 85; p < 0.05). Eutrophic children and adolescents revealed a wider range of interests, better capacity for social adaptability as well as greater speed and dexterity. Although weak, there was a positive correlation between income level, weight/stature relation (W/S) and IQ. There was no correlation between IQ and level of schooling. The eutrophic boys from higher income levels showed better perceptual and spacial organizing ability and a wider range of interests than those from the lower income groups. In spite of the fact that all the average IQ results presented consistently favored the eutrophic in relation to the obese, it is not possible to confirm one group's superiority over the other, due to the wide range of intervenient factors involved in the intelligence process.